Defesa da concorrência e comércio internacional no contexto do desenvolvimento: os cartéis de exportação como isenção antitruste - Domingues, Juliana Oliveira (2010)
The discussion about the relationship between competition defense and international trade is not a novelty. However, even in the globalized world there are countries that still lack the necessary expertise to deal with conducts of foreign agents that may distort the competition within their markets. International organizations have taken steps to discuss best practices and offer support to countries that intend to develop or improve their competition laws and policies and, in particular, to fight against the effects of anticompetitive practices. In the past it was argued that a set of multilateral competition rules should be created in view of international anticompetitive conducts and the use of artificial protectionist measures directed to annul the competition of imported products. However, the creation of multilateral competition rules has not been the focus of recent debates. The present study starts from the premise that the law is fundamental to development. The notion of development adopted herein is extensive, and based mainly in the new institutionalism (Douglass North) and in development as freedom (Amartya Sen). The analysis performed in this study was directed to export cartel practices that are antitrust exemptions in most jurisdictions and may be harmful to development. Export cartels may generate international trade distortions, especially in less developed or developing countries that do not have the expertise to handle such conducts. This theme has not been sufficiently debated even because it is a very particular conduct that relies on governmental support more often than not. Notwithstanding, in light of the need to foment development and based on the premises adopted in the present study, it is clear that such theme should be granted proper treatment considering the existing interface between competition and international trade. So, this study intends to deepen the analysis of export cartel exemptions and, within the development context that was adopted, indicate the need to create specific multilateral rules to regulate such practice